2018
DOI: 10.1159/000492731
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Mortality and Major Adverse Cardiovascular Events after Kidney Transplantation in the United States

Abstract: Background: Kidney transplantation (KT) is the treatment of choice for end-stage kidney disease. Cardiovascular disease is a major determinant of morbidity and mortality in patients with KT. Temporal trends in perioperative cardiovascular outcomes after KT are understudied, especially in light of an aging KT waitlist population. Methods: We performed a retrospective observational cohort study using the National Inpatient Sample for the years 2004–2013. All adult patients undergoing KT were identified using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Registry data from the USA [ 32 ] and Europe [ 33 ] point towards an ageing transplant recipient population. Single studies from the USA [ 34 ], Canada [ 35 ], Australia [ 36 ] and Europe [ 37 ] also report increasing recipient age. It is feasible that current evaluation strategies implemented in Austria promote the exclusion of ‘older and sicker’ ESRD patients from KT waiting list.…”
Section: Discussionmentioning
confidence: 99%
“…Registry data from the USA [ 32 ] and Europe [ 33 ] point towards an ageing transplant recipient population. Single studies from the USA [ 34 ], Canada [ 35 ], Australia [ 36 ] and Europe [ 37 ] also report increasing recipient age. It is feasible that current evaluation strategies implemented in Austria promote the exclusion of ‘older and sicker’ ESRD patients from KT waiting list.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of perioperative MACE were age �65 years (OR ¼ 2.14), Medicare as the primary payer (OR ¼ 1.51), diabetes (OR ¼ 1.46), recreational drug use (OR ¼ 1.72), pulmonary circulation disorders (OR ¼ 3.28), and malnutrition (OR ¼ 1.91). 44…”
Section: Discussionmentioning
confidence: 99%
“…For LDKT recipients, heart failure and diabetes were risk factors for poorer transplant survival. � Predictors of MACE: Goyal et al 44 This analysis of the NIS revealed predictors of MACE after KT to be age �65, Medicare as primary payer, diabetes, recreational drug use, pulmonary circulation disorders, and malnutrition.…”
Section: Kidney Transplantation (Kt)mentioning
confidence: 99%
“…There are very few randomized studies that have evaluated the benefit of coronary revascularization over standard medical therapy [ 18 ]. A recent study by Goyal et al [ 19 ] from the National Inpatient Sample in the US showed that rates of perioperative MACE after kidney transplantation remain low on an absolute level and the data suggest that post- operative MACE may be driven more by heart failure than acute coronary syndromes. Therefore, clinicians wrestle with the question of whether screening for occult ischemic heart disease is effective in preventing subsequent vascular events.…”
Section: Introductionmentioning
confidence: 99%